Perlindungan Hukum Hak Cipta Software Program Komputer di Indonesia - Hasbir Paserangi (Fakultas Hukum Universitas Islam Indonesia, 2011)
The problem in this research is on how far Act No. 19 of 2002 on Copyright reflects the principles provided in TRIPs. Can this Act on Copyright be in synergy with the structure and legal culture of Indonesian society in order to create a legal system which can generate justice, benefit, and legal certainty? How is the form of copyright enforcement in computer software can create an effective legal protection. This is a normative legal research using some approaches which are statute approach, conceptual approach, and comparative approach. While empirical legal research uses sociological approach.The result of this research shows that principles and provisions in TRIPs related to copyrights had been adopted in Act No. 19 of 2002 on Copyright. The concept of Intellectual Property Right is not yet in synergy optimally with culture and legal awareness of Indonesian society. Legal enforcement procedure on copyright in various countries has some similarities which generally includes private procedure and criminal procedure and administrative procedure.